Pengaruh Skill Guru Terhadap Efektivitas Belajar Peserta Didik Kelas III MI Roudlotus Salafiyah Di Era Society 5.0 - Husna, Riska Latifatul (Ta'lim : Jurnal Multidisiplin Ilmu, 2023)
The era of Society 5.0 in the world of education emphasizes character, moral and exemplary education. This is because the knowledge possessed can be replaced by technology while the application of soft skills and hard skills possessed by each student cannot be replaced by technology. In this case, readiness is needed in terms of competency-based education, understanding and utilization of IoT (Internet of Things), the use of virtual or augmented reality and the use and utilization of AI (Artificial Intelligence). This is where the collaboration between teachers and students in the learning process lies. This collaboration or blending process is expected to be able to end the learning system that has been teacher-centric so far. The formulation of the problem in this paper is to find out how the influence of teacher skills on the effectiveness of student learning in the era of society 5.0, especially in MI Roudlotus Salafiyah Pucung Lor Ngantru Tulungagung. The research method that the author uses in this research is to use a qualitative descriptive approach. Based on the discussion above, it can be concluded that the teacher's skills affect the learning effectiveness of third grade students at MI Roudlotus Salafiyah. In this case, readiness is needed in terms of competency-based education, understanding and utilization of IoT (Internet of Things), the use of virtual or augmented reality and the use and utilization of AI (Artificial Intelligence). In addition to these three things, teachers must also have the skills and have leadership skills, digital literacy, communication, entrepreneurship, and problem solving in conducting learning in the era of society 5.0.